Criminal Liability of Doctors in Telemedicine Health Services - M. Ngurah Yogie Khrsna; I Wayan Wesna Astara; I Nyoman Gede Sugiarta; I Gusti Bagus Suryawan (Journal Equity of Law and Governance, 2026)
The criminal liability of doctors in telemedicine services often becomes a focal point in legal proceedings, especially when undesired outcomes occur for patients or their families. Meanwhile, inaccuracies in patient-provided information are sometimes overlooked or receive less attention. Law Number 17 of 2023 on Health serves as the legal foundation for clarifying criminal acts and the criminal liability of doctors in telemedicine services, particularly when issues arise from factors beyond their control, such as technological limitations, incomplete patient information, and the appropriateness of medical practice. This study aims to determine whether adverse outcomes from telemedicine services for patients or their families constitute criminal acts and can be held accountable under the law. The research employs legal methods with statutory and conceptual approaches. The findings reveal that patient dissatisfaction with services or doctor negligence may lead to legal issues classified as criminal acts. Actions considered criminal in telemedicine include those prohibited by law and subject to penalties under the Health Law. Criminal liability arises if a doctor’s error results in serious harm, such as adverse outcomes from diagnoses or treatments conducted without adequate physical examinations, making the doctor subject to criminal sanctions under applicable laws.